Arginine methylation of HSP70 regulates retinoid acid-mediated RARβ2 gene activation - Gao, Wei-wei; Xiao, Rong-quan; Peng, Bing-ling; Xu, Huan-teng; Shen, Hai-feng; Huang, Ming-feng; Shi, Tao-tao; Yi, Jia; Zhang, Wen-juan; Wu, Xiao-nan; Gao, Xiang; Lin, Xiang-zhi; et al. (Proceedings of the National Academy of Sciences - PNAS, 2015)
HSP70 proteins are well known as molecular chaperones involved in protein folding and quality control. Whether they also function in gene transcription on chromatin, and if so, how they are regulated, remains elusive. Here we report that HSP70 can also regulate gene transcription through its association with chromatin, distinct from its “classic” function as a molecular chaperone. The function of HSP70 in gene transcription is subject to regulation of an arginine methylation on a highly conserved residue in HSP70, which modulates the recruitment of a key component in the pre-initiation complex, and thus transcription initiation. The present study reveals an additional, previously overlooked function of HSP70 chaperone proteins, and links arginine methylation of nonhistone proteins to gene transcriptional regulation. Although “histone” methyltransferases and demethylases are well established to regulate transcriptional programs and to use nonhistone proteins as substrates, their possible roles in regulation of heat-shock proteins in the nucleus have not been investigated. Here, we report that a highly conserved arginine residue, R469, in HSP70 (heat-shock protein of 70 kDa) proteins, an evolutionarily conserved protein family of ATP-dependent molecular chaperone, was monomethylated (me1), at least partially, by coactivator-associated arginine methyltransferase 1/protein arginine methyltransferase 4 (CARM1/PRMT4) and demethylated by jumonji-domain–containing 6 (JMJD6), both in vitro and in cultured cells. Functional studies revealed that HSP70 could directly regulate retinoid acid (RA)-induced retinoid acid receptor β 2 (RAR β2 ) gene transcription through its binding to chromatin, with R469me1 being essential in this process. HSP70’s function in gene transcriptional regulation appears to be distinct from its protein chaperon activity. R469me1 was shown to mediate the interaction between HSP70 and TFIIH, which involves in RNA polymerase II phosphorylation and thus transcriptional initiation. Our findings expand the repertoire of nonhistone substrates targeted by PRMT4 and JMJD6, and reveal a new function of HSP70 proteins in gene transcription at the chromatin level aside from its classic role in protein folding and quality control.